Protein extract and activity antioxidant of corn (Zea mays) and sorghum (Sorghum bicolor L. Moench) grains - Prado, D. M. F. (2016)
Brazil is a major producer of grains, such as sorgh um and corn, which are used for export. Sorghum and corn grains have in its composition 9.5% and 9. 8 protein, respectively. Proteins are the most abundant and most diverse functions in living syste ms molecules. Currently, food proteins are increasingly recognized as a source of beneficial b ioactive peptides, and they are physiologically released during digestion. The aim of the work was to evaluate the protein extraction (four methods) and antioxidant activity of sorghum and corn grains . The proximal composition of grains was evaluated in relation to moisture, protein, lipids and ash contents, furthermore were quantified proteins concentration and antioxidant activity by FRAP method in the four extracts. The corn and sorghum grains were ground, homogenized (60 mesh) a nd stored at 5°C until analysis. The protein extraction utilized were: 1) dichloromethane/methan ol; 2) NH 4 HCO 3 (5mM, pH 8.0)/heat treatment; 3) water/ethanol/heat treatment; and 4) alkaline ex traction and precipitation. The corn and sorghum presented, protein 6.62% and 9.87%, lipids 4.45% an d 4.32%, moisture 8.87% and 8.23%, ash 0.96% and 1.15%, carbohydrates 79.01% and 76.41%, t otalizing a caloric value of 382.9 and 384.1 Kcal g -1 , respectively. The 2 and 3 methods in corn grain p resented highest protein content 133.16 and 142.24 μ g g -1 , respectively. In sorghum grain, methods 1, 2 and 3 presented protein content between 173.59 – 223.63 μg g -1 . The antioxidant activity of protein extracts was between 0.90 – 9.73μM of ferrous sulphate for corn and between 4.4 1 – 15.04μ M of ferrous sulphate for sorghum. The best results in the extraction using the method 3 for both grains could be due to the structure of proteins (zein and kafirins) which are soluble in a lcoholic solutions and insoluble in water. In conclusion, method 3 - water/ethanol/heat treatment (corn: 142.24 μg g -1 and sorghum: 223.63 μg g - 1 ) and method 3 (corn: 9.73 μM and sorghum: 15.04 μ M ) showed the best results for extracting protein and antioxidant activity, respectively. The protein extracts obtainedhave great potential as natural antioxidants